2011
DOI: 10.1007/s11064-011-0612-1
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphatidyl Inositol 3 Kinase-Glycogen Synthase Kinase 3β Pathway Mediates Bilobalide-Induced Reduction in Amyloid β-Peptide

Abstract: Bilobalide (BB), a sesquiterpenoid extract of Ginkgo biloba leaves, has been demonstrated to have neuroprotective effects. The neuroprotective mechanisms were suggested to be associated with modulation of intracellular signaling cascades such as the phosphatidyl inositol 3-kinase (PI3K) pathway. Since some members of intracellular signalling pathways such as PI3K have been demonstrated to be involved in amyloid precursor protein (APP) processing, the present study investigated whether BB has an influence on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…These data suggest that Tan IIA modulates platelet APP metabolism, possibly through ER signaling to PI3K/Akt. In accordance with this finding, our previous studies demonstrated that treatment of HT22 cells, SH-SY5Y cells stably expressing the Swedish mutant APP and ovariectomized rats with phytoestrogens, such as ginsenoside Rg1 and bilobalide, increases the secretion of sAPPα, enhances α-secretase activity and decreases the production of Aβ via ER-mediated PI3K/Akt signaling (11)(12)(13).…”
Section: Discussionsupporting
confidence: 77%
“…These data suggest that Tan IIA modulates platelet APP metabolism, possibly through ER signaling to PI3K/Akt. In accordance with this finding, our previous studies demonstrated that treatment of HT22 cells, SH-SY5Y cells stably expressing the Swedish mutant APP and ovariectomized rats with phytoestrogens, such as ginsenoside Rg1 and bilobalide, increases the secretion of sAPPα, enhances α-secretase activity and decreases the production of Aβ via ER-mediated PI3K/Akt signaling (11)(12)(13).…”
Section: Discussionsupporting
confidence: 77%
“…The automated high-throughput fluorescence-based imaging system demonstrated that the modulation of GSK-3 activity resulted in the perturbation of BACE1 localization/trafficking and extensive A secretion [97,98] whereas it seems no change in the AD brains for GSK 3 [99]. Several -secretase-related signaling pathway damage such as PI3K/AKT [100], Wnt [101], and Ca 2+ -dependent PKC [97,102] participate in the mechanism which -secretase-mediated by active GSK-3 leads to A production and accumulation.…”
Section: Gsk-3 and -Secretasementioning
confidence: 99%
“…Previous studies have indicated that MRTF-A elevates SRF-driven transcription and enhances its stimulation by brain-derived neurotrophic factor (BDNF) in primary cortical neurons, which can regulate SRF and hence contributes to specific gene expression. ERK1/2 as an important approach to AD, the pathway is being widely studied [29][30][31][32]. Previous studies have demonstrated that this pathway can be involved in the regulation of synaptic structure and function [31,33].…”
Section: Discussionmentioning
confidence: 99%
“…ERK1/2 as an important approach to AD, the pathway is being widely studied [29][30][31][32]. Previous studies have demonstrated that this pathway can be involved in the regulation of synaptic structure and function [31,33]. Activation of ERK1/2 pathway plays a key role in the regulation of functional and structural synaptic plasticity [34].…”
Section: Discussionmentioning
confidence: 99%